Current distributional status of the critically endangered Valcheta Frog: implications for conservation - Velasco, Melina Alicia (2016)
Fil: Velasco, Melina Alicia. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Zoología Vertebrados; Argentina